INTERAKSI MODEL PROBLEM BASED LEARNING BERBANTUAN PAPAN STATISTIKA TERHADAP KETERAMPILAN BERPIKIR KRITIS DALAM PEMBELAJARAN MATEMATIKA DI SEKOLAH DASAR - Yustina Neny Hastuti; Sutama, Sutama; Fathoni, Fathoni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to analyze the application of the Problem Based Learning (PBL) model assisted by statistical boards on critical thinking skills in elementary school mathematics learning. The research method used is quasi-experimental with a Pre-test Post-test Non-equivalent Control Group Design and employs purposive sampling technique. This study uses t-test data analysis. The research was conducted at SD Negeri 01 Anggrasmanis and SD Negeri 01 Gumeng in Karanganyar Regency. The application of the Problem Based Learning (PBL) model assisted by statistical boards has a significant impact on improving students' critical thinking skills in elementary school mathematics learning. Students who learn using the PBL model assisted by statistical boards show better improvement in critical thinking skills compared to those using conventional teaching methods.